Tata Kelola Dan Manajemen Keuangan Kelompok UMKM Di Desa Wisata - Yuli Ermawati; Pujianto Pujianto (LPPM Universitas Putera Batam, 2022)
Rural economic restructuring needs to be done immediately by utilizing village resources optimally with the entrepreneurial movement. One of the entrepreneurial movements is through the development of Tourism Villages. From the development of tourist villages, it can create or increase the role of MSME groups in the surrounding area. Weak financial literacy and access to capital for MSMEs often hinder their performance progress. With good financial management in the MSME group, it will improve the progress of their business. The purpose of this study was to identify and assess the level of effectiveness of financial governance and management in MSME groups in tourist villages. The research method used is qualitative by conducting observations and interviews with key informants in the tourist village of Sekapuk, Gresik. The results showed that the governance and financial management of the Mbok Inggih MSME group was based on a joint venture capital system and profit sharing through PKK management. This system can be said to be effective because it meets the Empowerment index. The Empowerment index assesses the effectiveness of MSME empowerment from 7 indicators